Conflicting identities between sex workers and motherhood: A systematic review. Issue 5 (28th May 2019) - Ma, Polly H.X.; Chan, Zenobia C.Y.; Loke, Alice Yuen
ABSTRACT: Being a mother is a traditional and central role for women. However, due to criminalization, social stigma and marginalized lifestyles, female sex workers (FSWs) may encounter disadvantages and social inequality. The aim of this review was to synthesize the results of studies focused on the challenges that FSWs face in negotiating their maternal identity with their stigmatized identity as sex workers. A total of 21 studies published from 2002 to 2016 were included in this review. Textual narrative and a thematic synthesis approach were adopted to synthesize key themes. Two common themes across countries were identified: conflicting identities between the jobs as sex workers and motherhood and responses to social expectations of ideal motherhood. Given the challenges that FSWs face with motherhood, comprehensive services, including health, family, social, and legal services, are needed to support FSWs as individuals and as mothers. A more holistic approach is recommended to address their physical, emotional, financial, and social problems faced by FSWs. Services should be offered in a friendly and non-judgmental manner. Further, to advance the health and safety of FSWs and their children, prostitution law may need to move toward decriminalization of sex work and educate the general public about respecting FSWs.